2017
DOI: 10.1073/pnas.1702724114
|View full text |Cite
|
Sign up to set email alerts
|

Inducing protein aggregation by extensional flow

Abstract: Relative to other extrinsic factors, the effects of hydrodynamic flow fields on protein stability and conformation remain poorly understood. Flow-induced protein remodeling and/or aggregation is observed both in Nature and during the large-scale industrial manufacture of proteins. Despite its ubiquity, the relationships between the type and magnitude of hydrodynamic flow, a protein's structure and stability, and the resultant aggregation propensity are unclear. Here, we assess the effects of a defined and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
129
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 96 publications
(139 citation statements)
references
References 49 publications
3
129
0
Order By: Relevance
“…There is thus a need to develop stress tests that more closely replicate the conformational ensemble generated during processing and transport. In light of this, we and others have shown that hydrodynamic extensional flow fields encountered during the nano‐filtration, pumping, and fill‐finish steps of bio‐processing can trigger protein aggregation (Charm & Wong, 1981; Dobson et al, 2017; Simon, Krause, Weber, & Peukert, 2011; Wolfrum, Weichsel, Siedler, Weber, & Peukert, 2017). Using a reciprocating extensional and shear flow device (EFD) (Figure 1a), we showed that extensional flow fields can induce the conformational unfolding/remodeling of bovine serum albumin (BSA, Figure 1b), leading to aggregation that was characterized and quantified by an array of biophysical techniques including DLS, NTA, and TEM (Dobson et al, 2017).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…There is thus a need to develop stress tests that more closely replicate the conformational ensemble generated during processing and transport. In light of this, we and others have shown that hydrodynamic extensional flow fields encountered during the nano‐filtration, pumping, and fill‐finish steps of bio‐processing can trigger protein aggregation (Charm & Wong, 1981; Dobson et al, 2017; Simon, Krause, Weber, & Peukert, 2011; Wolfrum, Weichsel, Siedler, Weber, & Peukert, 2017). Using a reciprocating extensional and shear flow device (EFD) (Figure 1a), we showed that extensional flow fields can induce the conformational unfolding/remodeling of bovine serum albumin (BSA, Figure 1b), leading to aggregation that was characterized and quantified by an array of biophysical techniques including DLS, NTA, and TEM (Dobson et al, 2017).…”
Section: Introductionmentioning
confidence: 90%
“…In light of this, we and others have shown that hydrodynamic extensional flow fields encountered during the nano‐filtration, pumping, and fill‐finish steps of bio‐processing can trigger protein aggregation (Charm & Wong, 1981; Dobson et al, 2017; Simon, Krause, Weber, & Peukert, 2011; Wolfrum, Weichsel, Siedler, Weber, & Peukert, 2017). Using a reciprocating extensional and shear flow device (EFD) (Figure 1a), we showed that extensional flow fields can induce the conformational unfolding/remodeling of bovine serum albumin (BSA, Figure 1b), leading to aggregation that was characterized and quantified by an array of biophysical techniques including DLS, NTA, and TEM (Dobson et al, 2017). By subjecting five other globular proteins that varied in sequence, size, and structure to such flow stresses, we demonstrated that the aggregation propensity of proteins differed based on their fold, sequence, and the fluid fields to which they are subjected (Dobson et al, 2017).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations